Resistive switching characteristics of manganese oxide thin film and nanoparticle assembly hybrid devices. (2nd May 2018) - Abbas, Haider; Park, Mi Ra; Abbas, Yawar; Hu, Quanli; Kang, Tae Su; Yoon, Tae-Sik; Kang, Chi Jung
Abstract: Improved resistive switching characteristics are demonstrated in a hybrid device with Pt/Ti/MnO (thin film)/MnO (nanoparticle)/Pt structure. The hybrid devices of MnO thin film and nanoparticle assembly were fabricated. MnO nanoparticles with an average diameter of ∼30 nm were chemically synthesized and assembled as a monolayer on a Pt bottom electrode. A MnO thin film of ∼40 nm thickness was deposited on the nanoparticle assembly to form the hybrid structure. Resistive switching could be induced by the formation and rupture of conducting filaments in the hybrid oxide layers. The hybrid device exhibited very stable unipolar switching with good endurance and retention characteristics. It showed a larger and stable memory window with a uniform distribution of SET and RESET voltages. Moreover, the conduction mechanisms of ohmic conduction, space-charge-limited conduction, Schottky emission, and Poole–Frenkel emission have been investigated as possible conduction mechanisms for the switching of the devices. Using MnO nanoparticles in the thin film and nanoparticle heterostructures enabled the appropriate control of resistive random access memory (RRAM) devices and markedly improved their memory characteristics.